2015
DOI: 10.1016/j.bbadis.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of thrombospondin1 and CD36 contributes to obesity-associated podocytopathy

Abstract: Obesity is associated with podocyte injury and the development of proteinuria. Elevated plasma free fatty acid is one of the characteristics of obesity and has been linked to podocyte dysfunction. However, the mechanisms remain unclear. In the current study, we examined the effect of saturated free fatty acid (FFA) on human podocyte apoptosis and function in vitro. The mechanism and its in vivo relevance were also determined. We found that FFA treatment induced human podocyte apoptosis and dysfunction, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 59 publications
2
32
0
Order By: Relevance
“…Tumor microenvironment, comprising of various proteins, nucleic acids and vesicles, plays a key role in cancer progression to metastasis. TSP1 is one of the extracellular matrix glycoproteins, generally secreted by endothelial cells, fibroblasts, smooth muscle cells, and regulates the signaling pathways of CD47, CD36 and TGF-β [32,33]. The present study demonstrated that TSP1 is one of the important components in carcinoma-derived exosomes and is most likely to be a key molecule responsible for the down-regulation of molecules such as ZO-1 and VE-cadherin involved in the maintenance of epithelial integrity.…”
Section: Discussionsupporting
confidence: 51%
“…Tumor microenvironment, comprising of various proteins, nucleic acids and vesicles, plays a key role in cancer progression to metastasis. TSP1 is one of the extracellular matrix glycoproteins, generally secreted by endothelial cells, fibroblasts, smooth muscle cells, and regulates the signaling pathways of CD47, CD36 and TGF-β [32,33]. The present study demonstrated that TSP1 is one of the important components in carcinoma-derived exosomes and is most likely to be a key molecule responsible for the down-regulation of molecules such as ZO-1 and VE-cadherin involved in the maintenance of epithelial integrity.…”
Section: Discussionsupporting
confidence: 51%
“…136 Similarly, in an adriamycin-induced nephropathy mouse model of focal segmental glomerulosclerosis, TSP1 expression increased in injured podocytes and led to CD36-dependent apoptosis via activation of the p38MAPK pathway. 137 In a model of diet-induced obesity, podocyte apoptosis and dysfunction were attenuated in TSP1-deficient and in CD36-deficient mice, suggesting that the interaction of TSP1 with CD36 contributes to obesity-associated podocytopathy 138 . Moreover, blocking TSP1 binding to CD36 using peptide treatment attenuated fatty-acid-induced podocyte apoptosis, suggesting that the TSP1/CD36 interaction mediates this process.…”
Section: [H2] Interactions With Thrombospondinmentioning
confidence: 99%
“…In addition to tubules, CD36 is also upregulated in podocytes during proteinuric injury in experimental models and human podocytes, and blockade of CD36 on podocytes in vitro led to an improvement in health with less apoptosis and oxidative stress. 12,22,137,138,190 Blockade of CD36-dependent pathways, therefore, holds great promise as a therapeutic strategy for a variety of kidney diseases.…”
Section: [H1] Cd36 As a Potential Therapeutic Targetmentioning
confidence: 99%
“…TSP1 binding to its receptor CD36 is involved in podocyte apoptosis. 81 TSP1 has a pro-inflammatory effect on macrophages by stimulating increased toll-like receptor 4 expression, which in turn induces tumor necrosis factor-α production in a manner blocked by peptides that prevent TSP1-CD36 binding. 82 TSP1 is a known inhibitor of angiogenesis through its ability to downregulate nitric oxide signaling downstream of binding to CD47, and the TSP1-CD47 pathway is well documented to exacerbate ischemiareperfusion injury.…”
Section: Tgf-β-independent Functions Of Tsp1 In Renal Fibrosismentioning
confidence: 99%